PENYULUHAN PEMANFAATAN LAHAN PEKARANGAN RUMAH TANGGA UNTUK KETAHANAN PANGAN DALAM MENCEGAH STUNTING DI DESA GALESONG KOTA KABUPATEN TAKALAR - Ardiansyah, muhammad ardiansyah; Tajuddin, Mustamin; Liswahyuni, Andi; Zulkifli, Andi Tenriawaruwaty A.R.; Malik, Abdul; Tampubolon, Irianti; Mahaji, Toga; Palad, Marliana; Suryani, Ida; Kardi, Cening (Jurnal Abdi Insani, 2025)
This community service program aims to improve community knowledge and skills in effectively utilizing home gardens to meet family food needs and support stunting prevention efforts. This activity was implemented through counseling, demonstrations, and mentoring for housewives and other family members. The material presented in the counseling included techniques for growing vegetables, fruits, and family medicinal plants (TOGA) in limited yard space, as well as information on balanced nutrition and the importance of obtaining adequate nutritional intake to prevent stunting. The results of this activity showed an increase in community knowledge and interest in utilizing their yard space. It is hoped that the productive use of yard space will have an impact on increasing family food security, improving community nutrition, and reducing stunting rates in Galesong Kota Village. The output of this activity showed an 80% increase in participant knowledge, as well as significant interest from the community in utilizing their yards. In addition, the formation of farmer groups is expected to support the program's sustainability and the exchange of information. It is hoped that the productive use of yards will help increase family food security, improve community nutrition, and reduce stunting rates in Galesong Kota Village. This program has the potential to be implemented in other villages with similar characteristics.   Keywords: Community Service, Food, Nutrition, Stunting, Gelesong